2020
DOI: 10.1039/d0dt01081b
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of N-oxide functionality into NbO-type MOFs for significantly enhanced C2H2/CH4 and CO2/CH4 separations

Abstract: Two NbO-type MOFs with N-oxide functionality immobilized in the pore surface display significantly enhanced C2H2/CH4 and CO2/CH4 separation performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 56 publications
4
39
0
Order By: Relevance
“…Among the three compounds, the ortho ‐dimethyl functionalized compound ZJNU‐96 exhibited the highest gravimetric C 2 H 2 uptake capacity, which is 6.2 % higher than those of its counterpart ZJNU‐95 functionalized with meta ‐methyl group at 298 K and 1 atm. The C 2 H 2 uptake capacity of ZJNU‐96 is at a high level among the C 2 H 2 adsorptive values reported for porous materials under the same conditions [2b,17a] . The density of C 2 H 2 stored in the bulk ZJNU‐96 material at 298 K and 1 atm is 0.154 g cm −3 , which is equivalent to the value corresponding to an imaginary storage condition of 146.7 atm and room temperature, and is 73.3 times the compression limit for safe C 2 H 2 storage at ambient conditions.…”
Section: Resultsmentioning
confidence: 70%
“…Among the three compounds, the ortho ‐dimethyl functionalized compound ZJNU‐96 exhibited the highest gravimetric C 2 H 2 uptake capacity, which is 6.2 % higher than those of its counterpart ZJNU‐95 functionalized with meta ‐methyl group at 298 K and 1 atm. The C 2 H 2 uptake capacity of ZJNU‐96 is at a high level among the C 2 H 2 adsorptive values reported for porous materials under the same conditions [2b,17a] . The density of C 2 H 2 stored in the bulk ZJNU‐96 material at 298 K and 1 atm is 0.154 g cm −3 , which is equivalent to the value corresponding to an imaginary storage condition of 146.7 atm and room temperature, and is 73.3 times the compression limit for safe C 2 H 2 storage at ambient conditions.…”
Section: Resultsmentioning
confidence: 70%
“…Obviously, the total adsorption volume of MoP@C‐14.1 is increased compared with the unmodified MoP, indicating that the effect of absorbent cotton on MoP is strengthened. Moreover, the hysteresis loop of MoP@C‐14.1 in the isotherm shift to P/P 0 values of 0.7–1.0, and the adsorption amount on the high‐pressure side is larger than unmodified MoP , . It hints that the slit pores may be formed by the accumulation of flake particles .…”
Section: Resultsmentioning
confidence: 95%
“…The compounds with N-oxide groups have several advantages over the parent pyridyl-N atom due to the presence of additional lone pairs in the N-oxide moiety, which could lead to enhanced interactions with solvent/guest molecules. For example, Xu et al showed that modified metal-organic frameworks with N-oxide moieties displayed enhanced C 2 H 2 and CO 2 adsorptions [35]. Compounds with pyridine-N-oxide moieties are an excellent organocatalyst in various racemic and enantioselective reactions and act as oxidant in various oxidation reactions [36].…”
Section: Introductionmentioning
confidence: 99%